The Occupational Profile of Women with Fibromyalgia Syndrome. (17th December 2015) - Pérez‐de‐Heredia‐Torres, Marta; Huertas Hoyas, Elisabet; Sánchez‐Camarero, Carlos; Pérez‐Corrales, Jorge; Fernández de‐las‐Peñas, César
Abstract: The aims of this study were to assess the functional level of women with fibromyalgia; to investigate the differences in the occupational activities between women with fibromyalgia and healthy women; and to analyse the perceived importance of occupational performance during self‐care, productivity and leisure activities. A cross‐sectional case control study was performed. Twenty women with fibromyalgia and 20 healthy women completed the Functional Independence Measure (FIM), the Canadian Occupational Performance Measure (COPM), a Numerical Pain Rating Scale, the Fibromyalgia Impact Questionnaire and the SF‐36 health survey. The Chi‐square test (χ2), the Student's t test and the Spearman's test were used on the data. The FIM revealed significant differences regarding several activities: personal hygiene, bathing and memory ( p  < 0.01). The COPM scores did not reveal significant differences between groups ( p  > 0.10). Women with fibromyalgia had higher disability and reduced quality of life and required greater assistance to perform specific activities of daily living, i.e. hygiene, than healthy women. This highlights the specific occupational therapy needs these women have for performing many basic activities and for improving their quality of life. Limitations of the study include the small sample size, the exclusion of male participants and the possible influence of the women's psychological status on the assessments performed. Findings should be generalized with caution. Copyright © 2015 John Wiley & Sons, Ltd.